FAKTOR -FAKTOR YANG MEMPENGARUHI PEMILIHAN ALAT KONTRASEPSI PADA AKSEPTOR KELUARGA BERENCANA - Septi Widiyanti; Yusro Hadi M; Sri Lestariningsih (Jurnal Medikes (Media Informasi Kesehatan), 2022)
The strategy to reduce fertility rates is through contraception to prevent pregnancy, but not all contraceptives are suitable for the physical health condition of the wearer. Active family planning participants in Metro City in 2020 amounted to 21917 (72.73%). The coverage of intrauterine contraceptive users in Metro City is 3439 (15.%), and the lowest is in the Karangrejo Health Center working area, which is 10.61% (106 out of 999 acceptors). This study aimed to determine the factors that influence the selection of contraceptives in family planning in Karangrejo Village. Methods: Quantitative research with a cross-sectional design, the population of family planning acceptors is 1374 family planning acceptors. With the results of the calculation of the sample size obtained, a sample of 94 respondents—was sampled with a simple random sampling technique. The data was collected using a questionnaire, and the analysis used univariate, bivariate, and multivariate multiple regression analysis. Results: The results of the bivariate test conducted on nine variables related to the use of IUD contraception only five variables, namely knowledge (p=0.03), occupation (p=0.002), economy (p=0.041), husband's support (p= 0.000) and health status during family planning (p= 0.000) while the other four variables were not related because the p-value was more than 0.05, namely education (p=0.210), number of children (p=0.670), history of the hereditary disease (p= 1,000) and confidence (p=1,000). In the multivariate analysis of variables, because the husband's support and maternal health status during family planning were constant, they were not included in the modeling. The final result of modeling obtained knowledge (p=0.07, 95% CI: 0.35 - 0.597) and occupation (p=0.12, 95% CI: 1.493 - 25,631). Conclusion: Results The most dominant factor is the husband's support factor, followed by maternal health during family planning, knowledge of contraceptives, and mothers who do not work / homemakers. Suggestion: In promoting the family planning program, the first step is to approach and educate the husbands of prospective acceptors. It is necessary to increase knowledge about family planning contraceptives, especially for wives who do not work or are homemakers.